Experience and challenges delivering hepatitis C virus treatment for people who inject drugs in Kenya - Boke, Joyce; Monroe-Wise, Aliza; Umutesi, Grace; Mbogo, Loice; Sambai, Betsy; Bukusi, David; Chohan, Bhavna; Scott, John; Gitau, Esther; Sinkele, William; Musyoki, Helgar; Herbeck, Joshua; et al. (Frontiers in Medicine, 2024)
Despite having a higher risk of hepatitis C virus (HCV) infections, people who inject drugs (PWID) in sub-Saharan Africa (SSA) have limited access to HCV treatment. There is scarce literature on treatment delivery modalities that overcome logistical and financial barriers. We utilized different service delivery modalities to provide direct-acting antivirals (DAAs) to PWIDs infected with HCV through methadone clinics and needle and syringe program (NSP) sites in Kenya. In collaboration with Kenya’s National AIDS and STI Control Programme (NASCOP), we enrolled individuals with active HCV infection confirmed by HCV RNA detection from methadone and NSP sites in Nairobi, Mombasa, and Kilifi counties. Liver function and hepatitis B virus (HBV) status were assessed at baseline. Those eligible for treatment were offered ledipasvir-sofosbuvir treatment provided by NASCOP through directly observed therapy (DOT). Participants completed a follow-up visit 12 weeks after completing treatment to measure sustained viral response (SVR-12). Challenges faced while delivering HCV treatment at participating sites included the limited availability and reliability of laboratory assays, and financial constraints faced by PWIDs to attend daily DOT. Based on our experience, strategies to deliver HCV treatment for PWID in Kenya should consider improving the availability of laboratory tests and prioritizing treatment through methadone centers to achieve good outcomes.